PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KREDIT PERBANKAN - Raditya Cahya Nugraha, 09.05.52.0086; Lisiantara, Greg. Anggana (Students Journal of Accounting and Banking, 2013)
Bank is a financial institution that serves as a financial intermediary. Banks accept deposits from the public money and then distribute it back in the form of loans. Loan portfolio allows the investment, distribution, and consumption of goods and services, considering all the activities are always associated with the use of money. This study aims to empirically examine the effect of third-party funds (DPK), capital adequacy ratio (CAR), Non Performing Loans (NPL), Return on Assets (ROA), Interest Rates and Inflation on bank credit.The population in this study is the banks listed on the Stock Exchange during the year 2009 to 2011. Based on the selection criteria in this study found 25 companies, which produce 75 Data pooling. The method of analysis used to analyze the influence of third-party funds (DPK), capital adequacy ratio (CAR), Non Performing Loans (NPL), Return on Assets (ROA), Interest Rates and Inflation on bank lending is multiple linear regression analysis. The results of this study it can be concluded that: third party funding (TPF) positive effect on bank lending. While the capital adequacy ratio (CAR), Non Performing Loans (NPL), Return on Assets (ROA), Interest Rates and Inflation does not affect the bank creditKeywords: Third Party Funds (TPF), capital adequacy ratio (CAR), Non Performing Loans (NPL), Return on Assets (ROA), interest rate, inflation and bank lending